Exploring the genetic factors of nitrogen use efficiency in potato - Miguel Ángel Mendoza-Bustamante; Aura Natalia Jiménez-Medrano; Johana Carolina Soto-Sedano; María Cecilia Delgado-Niño; Stanislav Magnitskiy; Gustavo Adolfo Ligarreto-Moreno; Teresa Mosquera-Vásquez (PLoS ONE, 2025)
Nitrogen is an essential nutrient for plants, used by farmers to increase the yield of crops. However, this practice increases greenhouse gases, negatively affecting the environment. Nitrogen Use Efficiency (NUE) is a trait that is beginning to be studied in some model species and in cereals due to its complex and novel trait nature. In potatoes, the information is limited. Therefore, this research can help to mitigate the environmental impact of nitrogen fertilizer use, reducing groundwater contamination and greenhouse gas emissions. The study of NUE at the genetic level, based on a diverse population in potato materials, will contribute to the understanding of the genetic architecture of the trait. This research evaluated NUE in a Solanum tuberosum diploid potato genetic diversity panel from the Phureja group. The characterization of the trait was carried out in substrate conditions, for low and high levels of nitrogen for both the vegetative and the reproductive phase. Eighteen variables associated with NUE were measured, nine under low nitrogen and nine under high nitrogen conditions. A GWAS was conducted, and a total of 21 QTNs were identified as strongly associated with 11 phenotypic variables related to NUE in potato, these QTNs explained between 0.08% and 2.7% of the observed phenotypic variation, along with a repertoire of 750 candidate genes associated with the trait. This research aimed to establish the basis for understanding the genetic architecture of NUE in Solanum tuberosum . Once the candidate genes are validated, they could be used to develop molecular tools and accelerate breeding programs aimed at improving NUE in Solanum tuberosum .